2022-RA-1174-ESGO Role of adjuvant therapy in intermediate-risk cervical cancer patients – SCCAN study sub-analysis. (20th October 2022) - Cibula, David; Akilli, Huseyin; van Lonkhuijzen, Luc RCW; Fagotti, Anna; Dostálek, Lukáš; Ortiz, David Isla; Meydanli, Mehmet Mutlu; Abu-Rustum, Nadeem R; Odetto, Diego; Landoni, Fabio; Presl, Jiri; Klat, Jaroslav; et al.
Abstract : Introduction/Background: The 'intermediate-risk' (IR) group of early-stage cervical cancer patients is characterised by negative pelvic lymph nodes and a combination of tumour-related prognostic risk factors such as tumour size ≥2 cm, presence of lymphovascular space invasion (LVSI), and deep stromal invasion. The role of adjuvant treatment in these patients remains controversial, based on a single randomised GOG 92 study performed more than 20 years ago. The objective of our study was to evaluate if adjuvant (chemo)radiation is associated with a disease-free survival benefit after radical surgery in patients with IR cervical cancer. Methodology: We analysed data from patients who met criteria for intermediate risk cervical cancer (tumour 2–4 cm +LVSI OR tumour size >4 cm; N0; no parametrial invasion; clear surgical margins), underwent primary surgical treatment with a curative intent between 2007 – 2016, and were registered in the international multicentre Surveillance in Cervical CANcer (SCCAN) study. Administration of the adjuvant treatment stratified the cohort in two subgroups in which oncological outcomes were evaluated and compared using log-rank test. Results: Of 692 patients included in the analysis, 274 (39.6%) patients received no adjuvant treatment (AT-) and 418 (60.4%) were treated with adjuvant radiotherapy or chemoradiotherapy (AT+). The 5-year disease-free survival was 83.2% and 80.3% ( P =0.365) and corresponding overall survival 88.7% and 89.0% ( P =0.281) in AT- and AT+ groups, respectively ( figure 1 ). Separate sub-group analyses in patients with tumour ≥4 cm and 2–4 cm +LVSI also did not reveal any significant survival benefit of combined treatment in either of the sub-groups. Adjuvant (chemo)radiotherapy was not identified as an independent prognostic factor in the cohort or any of the sub-groups. Conclusion: Radical surgery alone achieved equal disease-free and overall survival in patients with intermediate-risk, early-stage cervical cancer as compared with combined treatment composed of radical surgery and adjuvant (chemo)radiotherapy.